Unmet Supportive Care Needs of Jordanian Patients with Colorectal Cancer: A Cross-Sectional Survey - Raya Yousef Al-Husban; Rana Obeidat; Omar Shamieh (Elsevier, 2021)
Objective: Colorectal cancer (CRC) is ranked the second most common cancer diagnosed in both men and women in Jordan. This paper aims to explore the unmet supportive care needs (USCNs), and their predictors among Jordanian survivors with CRC. Methods: A cross-sectional descriptive correlational research design with a convenience sample of 180 patients with CRC was conducted. Participants completed the Supportive Care Needs Survey-Short Form 34. Results: Jordanian patients with CRC reported their highest perceived level of need in the information and psychological domains. Multiple linear regression revealed that income and the number of chemotherapy sessions were significant predictors in the physical and daily living domains. Age, type of surgical treatment, and type of clinical setting were significant predictors of USCN in the psychological, patient care and support, and the health system and information domains. Conclusions: The health-care systems should work to meet all the supportive care needs for patients with CRC, particularly the informational and psychological needs domains where patients express unmet needs. Special care should be given according to age, type of surgery, and the doses of chemotherapy received. This study further confirms a disparity in the care and support provided to Jordanian cancer patients with different health-care settings in the country.